The Importance of Character Education for Elementary School Students in Facing the Era of Globalization - Choliza, Siti Nur; Fauzia, Rahma (Journal of General Education Science, 2024)
Character education is very important for elementary school students in facing the era of globalization. The era of globalization allows children to interact with various cultures and different values. In situations like this, character education can help students develop cognitive, physical, social-emotional, creativity and spiritual dimensions. Character education aims to shape and develop Indonesian people who are devoted to God Almighty, obey applicable legal regulations, carry out interactions between cultures, apply the noble values of the nation's culture, and strengthen the spiritual, moral and ethical foundations as the pride of the Indonesian nation. By having good character, students will become responsible individuals and be able to lead society in a better direction in the future. Therefore, character education must be applied and practiced in everyday life so that it becomes a good habit.